Creation of the Agricultural Development Group (GDA) for Olive Growers in Elles Community, Kef region, Northwest Tunisia - Dhehibi, Boubaker; Souissi, Asma; Frija, Aymen; Belgacem, Maaouia; M. Oumer, Ali; Idoudi, Zied; Ouerghemmi, Hassen; Shiri, Zahra; Le, Quang Bao; Alary, Veronique; Rudiger, Udo; Majri, Rihab; et al. (International Center for Agricultural Research in the Dry Areas, 2024)
The report presents a detailed analysis of the establishment process and evolution of a farmers' association in the community of Elles, situated within the El Sers district of the Kef Governorate in the northwestern region of Tunisia. This initiative emerged from the need to address the socio-economic and environmental challenges faced by local olive growers, including fluctuating agricultural production and market prices, lack of irrigation water, climate variability. Olive cultivation is the primary agricultural activity in Elles region, but traditional farming methods and limited organizational structure have constrained the community’s agricultural potential. To address these challenges, the report highlights the establishment of an Agricultural Development Group (GDA) aimed at better organizing local olive farmers under a professional framework (farmers’ cooperative or association).